2006
DOI: 10.1111/j.1744-7348.2006.00078.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of blackberry chlorotic ringspot, a new virus species in subgroup 1 of the genus Ilarvirus found naturally infecting blackberry in the UK

Abstract: A mechanically transmissible virus was isolated from Bedford Giant blackberry plants showing chlorotic mottling and ringspot symptoms growing in Scotland. It infected several herbaceous test plants, many of them symptomlessly. This virus was also transmitted to several Rubus species and cultivars by graft inoculation with scions from the field-infected Bedford Giant plant. Most grafted plants were infected symptomlessly, but Himalaya Giant blackberry and the hybrid berry Tayberry developed symptoms similar to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…In addition, efficient purification and detection methods were developed. Phylogenetic analysis places GAMV in the genus Ilarvirus and more specifically in its subgroup 1, along with Tobacco streak virus (TSV), Strawberry necrotic shock virus (SNSV) (Tzanetakis et al 2004), Blackberry chlorotic ring spot virus (BCRV) (Jones et al 2006), and Parietaria mottle virus (PMoV) .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, efficient purification and detection methods were developed. Phylogenetic analysis places GAMV in the genus Ilarvirus and more specifically in its subgroup 1, along with Tobacco streak virus (TSV), Strawberry necrotic shock virus (SNSV) (Tzanetakis et al 2004), Blackberry chlorotic ring spot virus (BCRV) (Jones et al 2006), and Parietaria mottle virus (PMoV) .…”
Section: Introductionmentioning
confidence: 99%
“…EU distribution of non-EU viruses of Rubus (those viruses not reported in the EU are excluded from this table)Reported only once in the UK in a few plants of a single cultivar(Jones et al, 2006) …”
mentioning
confidence: 99%
“…Experiments have shown that the AMV CP and TSV CP can functionally substitute for one another. To examine the similarities in genome activation of RBDV, AMV and TSV, we tested whether expression of either the AMV, TSV or BCRV, a Rubus-infecting ilarvirus (Jones et al, 2006), CP gene from a binary plasmid could activate replication of agroinfiltrated RBDV RNA1 and RNA2. In each case, the CPs from these different viruses did not activate RBDV replication (Supplementary Table S2, Fig.…”
Section: Genome Activation By Rbdv But Not Amv and Ilarvirus Cpmentioning
confidence: 99%